2015
DOI: 10.1007/s00296-015-3304-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly destructive arthrosis of the hip joint in a young adult with systemic lupus erythematosus

Abstract: A 37-year-old female had been treated with corticosteroids for systemic lupus erythematosus clinically diagnosed at age 10. She suddenly had right hip pain without any antecedent trauma. Four months after the onset of pain, she visited her primary care physician. On magnetic resonance imaging, joint space narrowing at the weight-bearing area was already seen with bone marrow edematous lesions in both the femoral head and acetabulum. She was treated non-operatively; however, her pain continued to worsen in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Several potential risk factors have been proposed in the literature, including: (I) ageing; (II) female gender; (III) underlying health problems such as rheumatoid arthritis, diabetes mellitus and systemic lupus erythematosus; (IV) lower bone mineral density; (V) higher BMI; (VI) medicinal drug use including NSAIDs and corticosteroid; (VII) alcoholism (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24)27,29). In this study, we evaluated the risk factors and found the only prevalent factors were: (I) age greater than 60 years; (II) female gender; (III) underlying systemic disease such as rheumatoid arthritis, diabetes mellitus or systemic lupus erythematosus (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)23,24). There is insufficient evidence to support the relationship between BMD, BMI, medication and alcoholism and the o...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several potential risk factors have been proposed in the literature, including: (I) ageing; (II) female gender; (III) underlying health problems such as rheumatoid arthritis, diabetes mellitus and systemic lupus erythematosus; (IV) lower bone mineral density; (V) higher BMI; (VI) medicinal drug use including NSAIDs and corticosteroid; (VII) alcoholism (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24)27,29). In this study, we evaluated the risk factors and found the only prevalent factors were: (I) age greater than 60 years; (II) female gender; (III) underlying systemic disease such as rheumatoid arthritis, diabetes mellitus or systemic lupus erythematosus (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)23,24). There is insufficient evidence to support the relationship between BMD, BMI, medication and alcoholism and the o...…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated the risk factors and found the only prevalent factors were: (I) age greater than 60 years; (II) female gender; (III) underlying systemic disease such as rheumatoid arthritis, diabetes mellitus or systemic lupus erythematosus (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)23,24). There is insufficient evidence to support the relationship between BMD, BMI, medication and alcoholism and the occurrence of RDA (2,3,5,8,10,23,27,29). We did not find these factors to increase the risk of RDA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our investigation yielded 26 articles suggesting a potential correlation between RDC and endocrine [10][11][12][13], metabolic [13][14][15][16][17], hematologic [18,19], toxic [20][21][22], rheumatic conditions [23][24][25][26][27][28][29][30], or fractures/injuries [31][32][33][34][35] which we included in our analysis. Table I summarizes the clinical characteristics of patients with RDC associated with secondary conditions identified throughout the studies in the review, while Table II focuses specifically on RDC associated with RA.…”
Section: Search Methodology and Resultsmentioning
confidence: 99%